STUDI PEMBUATAN PROTOTIPE MATERIAL PISTON BERBASIS PISTON BEKAS DENGAN PENYISIPAN ST 60 DAN BESI COR SERTA PENAMBAHAN ADC 12 - Solechan -; Samsudi Raharjo (Universitas Muhammadiyah Semarang, 2010)
The use of aluminum in the automotive industry continued to increase since the year 1980, inparticular aluminum alloy used for the manufacture of pistons, engine blocks, cylinder heads andvalves. In this study uses the former gasoline engine piston waste recycled into the piston DaihatsuHi-Jet 1000 with the addition of ADC 12 and insert ST 60 and cast iron. Former Piston who hasthe composition 87.82 wt% Al, 7,76 wt% Si, 0.775 wt% Fe, 1.40 wt% Cu, 0.368 wt% Mg plusmaterial ADC 12 with insert ST 60 and cast iron which is used as a ring groove piston with gravitycasting process in the pouring temperature of 700oC, 750oC and 800oC. The specimens obtainedfrom the casting material above which is a prototype of the piston with insert. The results includethe test composition, microstructure, macro-and micro-hardness, shear test. The results of the mosthigh-Si alloy composition on the composition of 25% piston former plus 75% ADC 12 and ADC 12pure. Show the bonding of microstructure morphology best at the lowest temperature pouring withinsert cast iron that has the smallest layer interface and a good bond. Macro and micro hardnessADC 12 hardness highest on the composition of pure and pouring temperature of 700C withhardness 119.2 HVN and 61.95HRB. The highest shear strength of 27.79 MPa at casting withpouring temperature of 700oC, the composition of pure ADC insert cast iron. Keywords: prototype of a piston, a former waste material, Daihatsu hi-jet 100, gravity casting